Odpowiedź :
a=0,6m=6dm
b=6dm
1l=1dm³
120l=120dm³
V=Pp*H
V=1/2*a*b*H
120dm³=1/2*6dm*6dm*H
H=120/18dm
b=6dm
1l=1dm³
120l=120dm³
V=Pp*H
V=1/2*a*b*H
120dm³=1/2*6dm*6dm*H
H=120/18dm
Dane:
d1 = 0,6 m.
d2 = 6 dm = 0,6m.
V = 120 l = 120dm3 = 0,12 m3.
Rozwiązanie:
Pp = ½ d1 d2 = ½ 0,6m x 0,6m = ½ x 0,36m2 = 0,18m2.
V = Pp x H
Przekształcamy wzór, z którego otrzymamy wysokość graniastosłupa:
H = V/ Pp
H = 0,12 m3/0,18m2 = 0,67m = 67cm.
Odp. Wysokość graniastosłupa wynosi 67 cm.
d1 = 0,6 m.
d2 = 6 dm = 0,6m.
V = 120 l = 120dm3 = 0,12 m3.
Rozwiązanie:
Pp = ½ d1 d2 = ½ 0,6m x 0,6m = ½ x 0,36m2 = 0,18m2.
V = Pp x H
Przekształcamy wzór, z którego otrzymamy wysokość graniastosłupa:
H = V/ Pp
H = 0,12 m3/0,18m2 = 0,67m = 67cm.
Odp. Wysokość graniastosłupa wynosi 67 cm.